SINERGI ANTARA PEMERINTAH KOTA PEKANBARU DAN POLRESTA DALAM MELAKUKAN PENERTIBAN TEMPAT HIBURAN MALAM TAHUN 2020 - Muhammad Munawir; Khairul Anwar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Pekanbaru City as one of the Metropolitan cities whose people need a means to relieve fatigue from their daily activities. Thus the city of Pekanbaru has a place of public entertainment. Pekanbaru as one of the developing cities, has become one of the attractive industrial locations for business people, one of the rapidly growing industrial sectors in Pekanbaru at this time is the night club. The night club is a means of relaxing and also one of the tourist destinations in the metropolitan city. However, nightclubs violate the rules and regulations set by the government. So it is necessary to bring order to the police and the Pekanbaru city government to maintain order in the community. The formulation of this research is "How is the synergy between the Pekanbaru City government and the Polresta in controlling night entertainment venues in the city of Pekanbaru in 2020?" This study aims to determine the synergy between the Pekanbaru City government and the Polresta in controlling night entertainment venues in Pekanbaru City in 2020. This research is a type of descriptive research using a qualitative approach. The data collection technique in this study used interview, observation and documentation techniques, the data analysis used was qualitative method analysis. The findings that can be concluded are the synergy between the Pekanbaru City Police and the local government running optimally. In terms of communication, the Pekanbaru city government, in this case the Satpol PP, communicates with the Resort Police to conduct raids, verbal communication is through telephone and non-verbal communication in the form of letters or through the media. Coordination between the Polres and the Pekanbaru City government has also not run optimally. Even though the raids were carried out, there were still nightclubs that violated applicable regulations, such as drug trafficking in nightclubs. This means that the raid activities carried out by the Pekanbaru City government and the Pekanbaru City Police have not been carried out optimally. Keywords: Synergy, Communication, Coordination